Mudskippers and Their Genetic Adaptations to an Amphibious Lifestyle - Xinxin You; Min Sun; Jia Li; Chao Bian; Jieming Chen; Yunhai Yi; Hui Yu; Qiong Shi (Animals, 2018)
Mudskippers are the largest group of amphibious teleost fish that are uniquely adapted to live on mudflats. During their successful transition from aqueous life to terrestrial living, these fish have evolved morphological and physiological modifications of aerial vision and olfaction, higher ammonia tolerance, aerial respiration, improved immunological defense against terrestrial pathogens, and terrestrial locomotion using protruded pectoral fins. Comparative genomic and transcriptomic data have been accumulated and analyzed for understanding molecular mechanisms of the terrestrial adaptations. Our current review provides a general introduction to mudskippers and recent research advances of their genetic adaptations to the amphibious lifestyle, which will be helpful for understanding the evolutionary transition of vertebrates from water to land. Our insights into the genomes and transcriptomes will also support molecular breeding, functional identification, and natural compound screening.